Tracing the Idea of African Vernacular-Rooted Art: A Critical Analysis of Selected Contemporary South African and Nigerian Artists (2007-2016) - Ogbechie, Sylvester (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.